Trust Management VI 6th IFIP WG 11.11 International Conference, IFIPTM 2012, Surat, India, May 21-25, 2012. Proceedings - Dimitrakos, Theo.; Moona, Rajat; Patel, Dhiren; McKnight, D. Harrison; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 6th IFIP WG 11.11 International Conference, IFIPTM 2012, held in Surat, India, in May 2012. The 12 revised full papers presented together with 8 short papers and the abstracts of 4 keynote talks were carefully reviewed and selected from 51 submissions. Building on the traditions inherited from the iTrust and previous IFIPTM conferences, IFIPTM 2012 is a multi-disciplinary conference focusing on areas such as: trust models, social, economic and behavioural aspects of trust, trust in networks, mobile systems and cloud computation, privacy, reputation systems, and identity management.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Computers and Society; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction